Impact of exposure to patients with COVID-19 on residents and fellows: an international survey of 1420 trainees. Issue 1153 (21st October 2020) - Cravero, Anne L; Kim, Nicole J; Feld, Lauren D; Berry, Kristin; Rabiee, Atoosa; Bazarbashi, Najdat; Bassin, Sandhya; Lee, Tzu-Hao; Moon, Andrew M; Qi, Xiaolong; Liang, Peter S; Aby, Elizabeth S; et al.
ABSTRACT: Objectives: To determine how self-reported level of exposure to patients with novel coronavirus 2019 (COVID-19) affected the perceived safety, training and well-being of residents and fellows. Methods: We administered an anonymous, voluntary, web-based survey to a convenience sample of trainees worldwide. The survey was distributed by email and social media posts from April 20th to May 11th, 2020. Respondents were asked to estimate the number of patients with COVID-19 they cared for in March and April 2020 (0, 1–30, 31–60, >60). Survey questions addressed (1) safety and access to personal protective equipment (PPE), (2) training and professional development and (3) well-being and burnout. Results: Surveys were completed by 1420 trainees (73% residents, 27% fellows), most commonly from the USA (n=670), China (n=150), Saudi Arabia (n=76) and Taiwan (n=75). Trainees who cared for a greater number of patients with COVID-19 were more likely to report limited access to PPE and COVID-19 testing and more likely to test positive for COVID-19. Compared with trainees who did not take care of patients with COVID-19, those who took care of 1–30 patients (adjusted OR [AOR] 1.80, 95% CI 1.29 to 2.51), 31–60 patients (AOR 3.30, 95% CI 1.86 to 5.88) and >60 patients (AOR 4.03, 95% CI 2.12 to 7.63) were increasingly more likely to report burnout. Trainees were very concerned about the negative effects on training opportunities and professional development irrespective of the number of patients with COVID-19 they cared for. Conclusion: Exposure to patients with COVID-19 is significantly associated with higher burnout rates in physician trainees.